TATMaster - Psycholinguistic Divergences in Automatically Translated Texts - Rodrigues, Rafael Guimarães; Gomes, Rodrigo Reis; Rodrigues, Kaio Tavares; Guedes, Gustavo Paiva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
This work aims at creating a tool for analyzing the psychological and linguistic changes of texts translated from English into Brazilian Portuguese. The aim is to analyze differences between texts translated by automatic translators and human translators. For this purpose, a tool named LIWC is used in its Brazilian Portuguese version. LIWC is a tool that distributes lexical words in categories with linguistic and psychological characteristics. Through accounting the word categories, this work seeks to evaluate the percentage of psycholinguistic changes in automatically translated documents in comparison with a reliable translation performed by a human expert. In this way, this study aims to contribute to the improvement of the process of automatic translation of documents. Experimental results indicate promising directions for further research.